1967
DOI: 10.1029/jz072i016p04081
|View full text |Cite
|
Sign up to set email alerts
|

Radioisotopes as groundwater tracers

Abstract: The radioisotopes iodine 131 and tritium were used to determine the specific yield and permeability in an aquifer near a pumping borehole. The direction and rate of flow of natural groundwater was also determined by means of a free flow test, using these isotopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1968
1968
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Formulas 2 and 2a are important in their own right. The ratio of apparent flow rate .and average monitored flow velocity can be measured in the field in many instances [Wiebenga et al, 1967], and hence the specific yield can be estimated directly from field measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Formulas 2 and 2a are important in their own right. The ratio of apparent flow rate .and average monitored flow velocity can be measured in the field in many instances [Wiebenga et al, 1967], and hence the specific yield can be estimated directly from field measurements.…”
Section: Resultsmentioning
confidence: 99%
“…I)uring an investigation of aquifer parameters by means of radioisotopes in the Burdekin-i)elta area of Queensland, Australia [Wiebenga et al, 1967], it was observed that, when a radioactive solution was added to a borehole, the amount of lateral spreading during its passage to an adjacent pumped bore was very small. To improve the efficiency of field experiments, more information on both lateral and longitudinal spread of a solution flowing through a porous medium is required.…”
mentioning
confidence: 99%